Human cytomegalovirus UL23 inhibits immune cell migration and blocks antiviral immune cell responses by reducing the expression of chemokines CCL2 and CCL5 - Hankun Wang; Chunling Zhang; Moran Li; Wangchun Zhao; Jialin Wang; Yanhong Ran; Xiaoping Yang; Zemin Deng; Jun Chen; Hongjian Li (Virulence)
Human cytomegalovirus (HCMV) is a typical opportunistic human pathogen, which can endanger the lives of individuals with immune insufficiency or low immune function. One of the most effective immune mechanisms against HCMV in host cells is the production of antiviral cytokines. Chemokines are small secreted proteins produced by cell immune responses to inflammatory stimuli or viral infection and act as potent chemoattractants for granulocytes, monocytes, lymphocytes and other leukocytes, and thus play a significant role in antiviral defence. Viruses have also evolved multiple strategies to resist the host’s immune system while coexisting with the host. In this study, based on RNA sequencing transcriptome differential analysis, we found that HCMV encoded UL23 May specifically down-regulate chemokines Chemokine ligand 2 (CCL2) and Chemokine ligand 5 (CCL5). Next, we determined that UL23 could inhibit the expression of Chemokine CCL2 and CCL5 by mainly affecting the phosphorylation of IRF-3, and then inhibited the migration of immune cells and blocked the antiviral immune responses in the migration and co-culture assays of HCMV-infected cells with immune migration-related cells. In conclusion, these results highlight that UL23 plays an important role in the immune evasion of HCMV by specially inhibiting the expression of chemokines CCL2 and CCL5, impairing the recruitment of immune cells by infected host cells and helping the virus escape immune killing.